Korean Christian Missionaries in High-Risk Countries: Interaction with International Religious Networks and Domestic Response - Jung, Jihye (Journal for the scientific study of religion, 2024)
Why do some Christian foreign mission groups dispatch missionaries to some culturally and politically risky states where they face personal risks and political entanglements? Using world polity theory, I argue that local religious groups’ motivations are driven by their involvement in international religious networks, which mobilize missionaries to go to places such as Muslim countries. Based on 30 semistructured interviews with South Korean missionaries and leaders of churches and mission organizations, I illuminate that globally shared discourse of unreached people encouraged missionaries to volunteer to go to high-risk states. I also suggest that Korean religious actors did not passively accept the influence of the international discourse but also reconstructed the discourse. The study also highlights that a missionary's dual identity as a religious actor and another profession to get a visa in high-risk countries is bound up with the state's surveillance and potential persecution.